Cortical Inhibition and Plasticity in Major Depressive Disorder - Castricum, Jesminne; Birkenhager, Tom K.; Kushner, Steven A.; Elgersma, Ype; Tulen, Joke H. M. (Frontiers in Psychiatry, 2022)
Background: Major depressive disorder (MDD) is a severe psychiatric disorder that is associated with various cognitive impairments, including learning and memory deficits. As synaptic plasticity is considered an important mechanism underlying learning and memory, deficits in cortical plasticity might play a role in the pathophysiology of patients with MDD. We used Transcranial Magnetic Stimulation (TMS) to assess inhibitory neurotransmission and cortical plasticity in the motor cortex of MDD patients and controls. Methods: We measured the cortical silent period (CSP) and short interval cortical inhibition (SICI), as well as intermittent theta-burst stimulation (iTBS), in 9 drug-free MDD inpatients and 18 controls. Results: The overall response to the CSP, SICI, and iTBS paradigms was not significantly different between the patient and control groups. iTBS induction resulted in significant potentiation after 20 minutes in the control group (t(17)=-2.8, p=0.01), whereas no potentiation was observed in patients. Conclusions: We did observe plasticity deficits, but found no evidence for medium-to-large effect size differences in CSP and SICI measures in severely depressed drug-free patients, suggesting that reduced cortical inhibition is unlikely to be a robust correlate of the pathophysiological mechanism in MDD. However, these findings should be interpreted with caution due to the high inter-subject variability and the small sample size. Significance: These findings advance our understanding of neurophysiological functioning in drug-free severely depressed inpatients.